Normal tension glaucoma: A dynamic optical coherence tomography angiography study - Van Eijgen, Jan; Heintz, Alexander; van der Pluijm, Claire; Delporte, Margaux; De Witte, Dries; Molenberghs, Geert; Barbosa-Breda, João; Stalmans, Ingeborg (Frontiers in Medicine, 2023)
Purpose Vascular dysregulation seems to play a role in the pathogenesis of glaucoma, in particular normal tension glaucoma (NTG). The development of optical coherence tomography angiography (OCTA) enabled the measurement of the retinal microvasculature non-invasively and with high repeatability. Nonetheless, only a few studies transformed OCTA into a dynamic examination employing a sympathomimetic stimulus. The goal of this study was to use this dynamic OCTA exam (1) to differentiate healthy individuals from glaucoma patients and (2) to distinguish glaucoma subcategories, NTG and high-tension primary open angle glaucoma (POAG). Methods Retinal vessel density (VD) in NTG patients (n = 16), POAG patients (n = 12), and healthy controls (n = 14) was compared before and during a hand grip test with a hydraulic dynamometer. Results At baseline, mean peripapillary VD was lower in POAG and NTG (42.6 and 48.5%) compared to healthy controls (58.1%; p < 0.001) and higher in NTG compared to POAG (p = 0.024) when corrected for mean arterial pressure (MAP). Peripapillary and macular (superficial and deep) VD differences were found for gender, age, and baseline MAP. No change in VD occurred (pre-/post-stimulus) in any of the groups. Conclusion Retinal VD loss in glaucoma patients was confirmed and the necessity to correct for gender, age and especially MAP was established. Although replication in a larger population is necessary, OCTA might not be the most suitable method to dynamically evaluate the retinal microvasculature.